Evaluation of the antioxidant effect of polyphenolic extract of mango almond (Mangifera indica Var. Magdalena river) - Salazar-Beleño, Ana Milena; Paz-Díaz, Héctor Julio; Carreño-Castaño, Leidy Andrea; Pacheco-Valderrama, Mónica María; Murillo-Méndez, Cristian Jahir (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Polyphenolic extracts emerge as an alternative source to produce natural antioxidants. These can be present in fruit residues such as those from mango (Mangifera indica L.), giving added value to these residues and reducing the environmental impact that they can generate. The objective of this research work was to evaluate the inhibition of polyphenol oxidase (PPO) in a food matrix using polyphenolic extract obtained from the mango almond (Mangifera indica var. Magdalena river) as an inhibitor; observing the change of the color tone in time. For the extraction of polyphenols, ethanol at 57% (v/v) was used in a solute:solvent ratio 1:5 at 67 °C, for 60 minutes applying ultrasound waves for a greater extraction of polyphenols. The total polyphenol content of the polyphenolic extracts was determined by the Folin-Ciocalteu method. The evaluation of the inhibition of PPO on apple as a food matrix (Malus domestica var. Royal gala) was carried out, under natural storage conditions at 5 and 25 °C. Color tonality was recorded with photographic evidence at 30 minutes time intervals for 2 hours. Treatment with polyphenolic extract obtained satisfactory inhibition results compared to the ranges of the samples without treatment. Also, PPO inhibition was more effective using polyphenolic extract compared to ascorbic acid at the same concentration.